(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The diagnostic sensitivity of a test for a particular disease is defined as the percentage of cases of truly positive test results in patients with that particular disease. In ideal cases, the sensitivity is 100%. This means that each patient has a pathological value of the parameter under study corresponding to his disease, i.e. there are no false-negative results [7,9,11,12].